2020
DOI: 10.1002/cre2.314
|View full text |Cite
|
Sign up to set email alerts
|

Cell invasion, RAGE expression, and inflammation in oral squamous cell carcinoma (OSCC) cells exposed to e‐cigarette flavoring

Abstract: Objective Electronic cigarettes have given rise to a new, largely unregulated market within the smoking industry. While generally supposed to be less harmful than traditional tobacco smoke, awareness of the biological effects of electronic cigarette liquid is still scarce. Our objective was to determine the impact of electronic cigarette flavoring and nicotine on gingival squamous cell carcinoma invasion, RAGE expression, and the elaboration of pro‐inflammatory molecules. Methods and Materials Gingival and ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
1
15
0
1
Order By: Relevance
“…in fact, the World Health Organization has stated eCig vaping should not be recommended until its true toxicity profile have been properly established (Food and Drug Administration, HHS, 2016). Previous studies in our laboratory showed diverse inflammatory and invasive effects employed by OSCCs when treated with eCig liquid and nicotine (23). This research suggested a flavor and nicotine dependent regulation of OSCC biology.…”
Section: Discussionsupporting
confidence: 62%
“…in fact, the World Health Organization has stated eCig vaping should not be recommended until its true toxicity profile have been properly established (Food and Drug Administration, HHS, 2016). Previous studies in our laboratory showed diverse inflammatory and invasive effects employed by OSCCs when treated with eCig liquid and nicotine (23). This research suggested a flavor and nicotine dependent regulation of OSCC biology.…”
Section: Discussionsupporting
confidence: 62%
“… 172 , 173 In the larynx, rats exposed to e‐cig aerosols showed early evidence of hyperplasia and metaplasia of the mucosa, 174 although the results were not statistically significant in this limited study, and increases in IL‐4. 175 In addition, both nicotine‐containing and nicotine‐free e‐juice have been found to cause biologic disruptions including oxidative stress, DNA breakage, metanuclear anomalies, liposomal dysfunction, and solvent and lipid accumulation, and cytotoxicity in human gingival fibroblasts, 67 , 176 , 177 , 178 , 179 , 180 vocal fold epithelial cells and fibroblasts, 181 , 182 head and neck squamous cell carcinoma cell lines, 67 , 183 , 184 , 185 noncancerous oral and oropharyngeal epithelial cells, 139 , 178 , 186 , 187 , 188 , 189 , 190 , 191 , 192 middle ear epithelial cells, 193 , 194 , 195 nasal epithelial cells, 196 , 197 and organotypic cultures/organoids. 178 , 182 , 197 Interestingly, a recent study found that oral cancer cells exposed to e‐cig aerosols increased cell resistance to cisplatin through changes in drug transporters, suggesting a mechanism for e‐cig‐induced chemotherapy resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-six studies investigated the effects of flavored e-cigarettes. 12,14,[16][17][18]22,26,28,30,[32][33][34][37][38][39][40]47,50,52,56,58,59,61,63,64 The most commonly studied flavors were tobacco and mint/menthol, which appeared in 9/26 and 4/26 studies, respectively. One study 22 compared the effects of 10 different flavored e-liquids versus unflavored e-liquid of the same brand on oral epithelial cells and showed that, in general, flavored e-liquids (±nicotine) were associated with increased oxidative stress, lipid peroxidation, cytotoxicity, and micronuclei formation compared to unflavored e-liquid.…”
Section: Histologicalmentioning
confidence: 99%